Analisis Faktor-Faktor Yang Mempengaruhi Usia Harapan Hidup Di Kota/Kabupaten Jawa Tengah - Brina Azalia, Denti (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the factors influencing Life Expectancy across regencies and cities in Central Java Province during the 2021–2024 period, focusing on education and economic dimensions as key components of the Human Development Index. The research employs a quantitative explanatory approach using panel data from eight selected regencies/cities in Central Java. The independent variables are Expected Years of Schooling and Gross Regional Domestic Product (GRDP) per capita, while the dependent variable is Life Expectancy. Panel data regression analysis is conducted, with model selection determined through the Chow test, Hausman test, and Lagrange Multiplier test. The results indicate that the Random Effect Model (REM) is the most appropriate estimation method. Partially, Expected Years of Schooling has a positive and significant effect on Life Expectancy, whereas GRDP per capita does not show a significant effect. Each additional year of expected schooling increases Life Expectancy by more than one year, highlighting the crucial role of education in improving public health and quality of life. Simultaneously, the independent variables significantly affect Life Expectancy, with the model explaining 79.26 percent of its variation. These findings emphasize that improvements in educational quality play a more dominant role than economic factors in enhancing Life Expectancy in Central Java.